2007
DOI: 10.1158/1078-0432.ccr-05-2706
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Detection of Micrometastases in Pelvic Lymph Nodes in Patients with Clinically Localized Prostate Cancer by Real-time Reverse Transcriptase-PCR

Abstract: Purpose: Routine pathologic examination can miss micrometastatic tumor foci in the lymph nodes of patients with prostate cancer, resulting in confusion during tumor staging and clinical decision-making. The objective of this study was to clarify the significance of micrometastases in pelvic lymph nodes in patients who underwent radical prostatectomy for prostate cancer. Experimental Design:The expression of prostate-specific antigen (PSA) and prostate-specific membrane antigen (PSMA) in 2,215 lymph nodes isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…Using the database and sample library of the mass screening in Changchun, Mao et al [22] detected PSA mRNA and its protein expression by mononuclear cells in the peripheral blood of patients. This method can indirectly reflect prostate cancer with micro-metastases [23]. This study showed that although some patients were asymptomatic and did not see their physician, the presence of PSA mRNA and protein indicated micro-metastasis.…”
Section: Prostate Cancer Was Diagnosed At Late Stages In the United Smentioning
confidence: 93%
“…Using the database and sample library of the mass screening in Changchun, Mao et al [22] detected PSA mRNA and its protein expression by mononuclear cells in the peripheral blood of patients. This method can indirectly reflect prostate cancer with micro-metastases [23]. This study showed that although some patients were asymptomatic and did not see their physician, the presence of PSA mRNA and protein indicated micro-metastasis.…”
Section: Prostate Cancer Was Diagnosed At Late Stages In the United Smentioning
confidence: 93%
“…Real-time RT-PCR was performed using a sequence detector (Abi Prism 7700; PE Applied Biosystems, Foster City, CA, USA) based on the Taq Man assay according to the manufacturer's instructions, as previously described (12). The specimens were analyzed in triplicate and the mean values were used for quantification.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…Real-time RT-PCR was performed using a Sequence Detector (ABI PRISM 7700, PE Applied Biosystems, Foster City, CA) based on the TaqMan assay according to the manufacturer's instructions as described previously (11). All specimens were analyzed in triplicate and the mean values were used for quantification.…”
Section: Pc3mentioning
confidence: 99%